Post-flowering night respiration and altered sink activity account for high night temperature-induced grain yield and quality loss in rice (Oryza sativa) - Bahuguna, Rajeev N.; Solis, Celymar A.; Shi, Wanju; Jagadish, Krishna S.V. (Wiley, 2017)
High night temperature (HNT) is a major constraint to sustaining global rice production under future climate. Physiological and biochemical mechanisms were elucidated forHNT‐induced grain yield and quality loss in rice. Contrasting rice cultivars (N22, tolerant; Gharib, susceptible;IR64, high yielding with superior grain quality) were tested under control (23°C) andHNT(29°C) using unique field‐based tents from panicle initiation till physiological maturity.HNTaffected 1000 grain weight, grain yield, grain chalk and amylose content in Gharib andIR64.HNTincreased night respiration (Rn) accounted for higher carbon losses during post‐flowering phase. Gharib andIR64recorded 16 and 9% yield reduction with a 63 and 35% increase in average post‐flowering Rn underHNT, respectively.HNTaltered sugar accumulation in the rachis and spikelets across the cultivars with Gharib andIR64recording higher sugar accumulation in the rachis.HNTreduced panicle starch content in Gharib (22%) andIR64(11%) at physiological maturity, but not in the tolerantN22. At the enzymatic level,HNTreduced sink strength with lower cell wall invertase and sucrose synthase activity in Gharib andIR64, which affected starch accumulation in the developing grain, thereby reducing grain weight and quality. Interestingly,N22recorded lower Rn‐mediated carbon losses and minimum impact on sink strength underHNT. Mechanistic responses identified will facilitate crop models to precisely estimateHNT‐induced damage under future warming scenarios.